Adult Educators in the Face of Crises in Europe : Managing Challenges, Shaping Identities and Changing Cultures - Larissa Jõgi; George K. Zarifis; Susanne Lattke; Maria N. Gravani (Brill, 2025)
This book explores the evolving identities, practices and challenges faced by adult educators across Europe in the context of recent crises, including the COVID-19 pandemic, the war in Ukraine, and economic and social upheavals. These events have reshaped the educational landscape, disrupted adult learning and demanded rapid adjustments from adult educators. The book examines how these crises impact educators'identities, agency, and professional practice, particularly considering the precarious working conditions many face. Through empirical studies and theoretical reflections, the book investigates how adult educators navigate these turbulent times, addressing identity formation, professionalisation, and adaptation, while highlighting the ethical and social dimensions of their work. Contributors are: Anna Anastasopoulou, Olena Anishchenko, Nataliia Avsheniuk, Carmel Borg, Brigitte Borsche, Maria Brown, Maria N. Gravani, Larissa Jõgi, Kristi Jüristo, Katrin Karu, Evangelia Koutoulianou, Susanne Lattke, Borut Mikulec, Stephen O'Brien, Eleni Papaioouann, Halliki Põlda, Cynne Põldäär, Ilona-Evelyn Rannala, Maria Santa and George K. Zarifis.